Rancang Bangun Water Treatment di Atas Kapal dengan Reverse System Menggunakan Atmega 2560 - Bagus Indra Pramana Widya Putra; Edi Kurniawan; Frenki Imanto (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Ships as an important means of transportation require the availability of good quality fresh water to meet the daily needs of the crew. Because the quality of fresh water that does not meet the standards can interfere with the activities of the crew. This research aims to build a water treatment system on board controlled by ATMEGA 2560 microcontroller. The system is equipped with turbidity sensor SEN0189, TDS sensor SEN0244, and PH sensor SEN0161 to monitor the freshwater quality. The process of working this tool by treating fresh water which then the parameters are detected by the PH sensor, TDS sensor, and turbidity sensor which then the detection results are displayed on the LCD monitor, and the buzzer and LED turn on when the condition of the fresh water parameters does not meet the standards. The methodology and design of this system will be carried out with experimental research methods where in this method at least one variable is manipulated to study the cause-and-effect relationship. The results of testing water treatment using ATMEGA 2560 show that the system can work optimally in treating fresh water. And the accuracy of the PH sensor, TDS sensor, and turbidity sensor is quite accurate with the difference in error with the comparison measuring instrument less than 5%.